Analysis Of Theological Perspectives On Christian Contributions In Building Harmony Social And Peace In Public Toraja - Benny Agustinus Triangga Prayitno; Stefanus Dully; Donny Efendy Kurniawan (Jurnal Mamangan, 2024)
This research examines the contribution of Christianity to harmony and peace in Toraja society. This type of research uses a qualitative approach using literature studies (Literature). This research aims to find out the theological perspectives on the contribution of Christianity in building social harmony and peace in society. The results of this study indicate that Christianity plays an important role in shaping values that support peace and social harmony in Toraja society. In this case, it brings values that can be applied in the social context of Toraja culture, such as love, forgiveness and humility. These concepts form the basis for building peace and harmony in society. In addition, Christianity also provides motivation and moral support for individuals to be involved in efforts to build peace and harmony in society. This research suggests that the church continues to develop strategic approaches in efforts to build peace in Toraja society.